Gallbladder Ascariasis Presenting as Acalculous Biliary Colic - Carmen A Urbina; Luigi G Cubeddu; Luigi X. Cubeddu (HCA Healthcare Journal of Medicine, 2026)
We detail a case of gallbladder ascariasis, presenting as an acute episode of acalculous biliary colic, nausea, bloating, an unremarkable abdominal ultrasound, and negative helminth and protozoa stool smears. A follow-up ultrasound provided unexpected images consistent with gallbladder infection by Ascaris lumbricoides. Repeat ultrasonography performed 10 days after anthelmintic therapy showed no live worms and 2 newly appearing echogenic areas suggestive of gallbladder calculi that were confirmed following elective cholecystectomy. The case course highlights key clinical, diagnostic, and management considerations in gallbladder ascariasis and underscores the value of repeated ultrasonographic evaluation in affected patients.